Comparative Analysis of Consumer Preferences in Online Shopping on Shopee and Lazada in Medan - Panjaitan, Santi Rohdearni; Sitanggang, Augustinus Suryadi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to determine and analyze the differences in influence on consumer preferences in online shopping at Shopee and Lazada in the city of Medan. The type of research used is quantitative. The research population is the community in the area around the city of Medan who use the Shopee and Lazada e-commerce applications in 2023 and the determination of the number of samples in this research is using the purposive sampling method with the number of samples being 100. The data source for this research is primary data using an instrument. research in the form of a questionnaire. The data collection method used is survey research. This research uses multiple linear regression analysis for statistical analysis and the regression model has been tested first in the classic assumption test. The research results state that there are differences in consumer preferences for online shopping at Shopee and Lazada in the city of Medan. Product diversity and website quality are important sales tools and play a major role in establishing communication between consumers and are good for use as sales media.